2018
DOI: 10.1002/jcb.27350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on Sertoli cell proliferation

Abstract: Resveratrol (RSV), a polyphenolic compound largely found in red grape skin, has been used as a nutritional supplement as it exhibits beneficial health effects, such as anticancer, cardioprotective, antiaging, and anti-inflammatory. Particularly, it has been shown that it participates in the mechanisms involved in cell proliferation. Sirtuin 1 (SIRT1) is considered a well-known RSV effector. Noteworthy, Sirt1-knockout animals are infertile. The aim of this study was, first, to determine whether RSV has any effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(165 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, the cell cycle inhibitor p21 is involved in cell cycle arrest and in the maturation of Sertoli cells. Retinoic acid, the thyroid hormones, and signaling proteins such as AMPK and Sirtuin 1 increase p21 expression as part of their anti‐proliferative action 24,40,41 . In the present study, we show that Sertoli cells isolated from metformin‐treated animals present reduced Ccnd1 and Ccne2 mRNA levels and increased Cdkn1a mRNA levels.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, the cell cycle inhibitor p21 is involved in cell cycle arrest and in the maturation of Sertoli cells. Retinoic acid, the thyroid hormones, and signaling proteins such as AMPK and Sirtuin 1 increase p21 expression as part of their anti‐proliferative action 24,40,41 . In the present study, we show that Sertoli cells isolated from metformin‐treated animals present reduced Ccnd1 and Ccne2 mRNA levels and increased Cdkn1a mRNA levels.…”
Section: Discussionsupporting
confidence: 56%
“…Activation of SIRT1 decreased cyclin D1 and D2 levels and increased p21Cip1 mRNA levels. SIRT1 activation also decreased c-Myc transcriptional activity (189). Remarkably, TH regulate SIRT1 expression and activity in different experimental models (190192).…”
Section: Main Factors Involved In Cessation Of Proliferation and In Mmentioning
confidence: 99%
“…Liu et al reported that the administration of resveratrol could ameliorate Microcystin‐leucine arginine‐induced Sertoli cell apoptosis (Liu et al, 2018). Noteworthy, Sirt1‐knockout animals are infertile (Gorga et al, 2018). Also, the deficiency of SIRT1 in yak testis caused the impairment of testicular development (Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%